Evaluation of the photosynthetic response of Ginkgo biloba as an urban tree to air pollution, soil salinity, and excess humidity - Matsuura, Takumi; Okugawa, Souma; Yamakita, Eri; Kiyomizu, Takashi; Tsutsui, Yuuri; Kume, Atsushi; Hanba, Yuko T. (Frontiers in Plant Science, 2026)
IntroductionAlthough the use of G. biloba as a roadside tree has been slightly declined in Japan, the number of G. biloba planted in Europe and other countries has been increasing in recent years because of its high adaptability to diverse environmental stresses. To re-evaluate the value of G. biloba as an urban tree, we focused on three environmental stress factors that can be notable in urban environments in Japan: (1) air pollution, (2) soil salinity, and (3) excess humidity. We evaluated the leaf photosynthetic functions of G. biloba in response to the above three types of environmental stresses.MethodsWe compared the responses of G. biloba to air pollution (Experiment 1) and to soil salinity (Experiment 2) with those of Rhododendron × pulchrum, the most commonly used roadside shrub in Japan. For experiment 1, we collected branches of G. biloba and R. pulchrum, which were planted as roadside trees in Kyoto city, in 2014 and 2017 to measure their photosynthetic functions. For experiments 2, we conducted a growth experiment with G. biloba and R. pulchrum seedlings, supplying 50 mM NaCl for three weeks. Experiment 3, an excess humidity experiment, was conducted only for G. biloba seedlings from 2020 to 2022. It involved a two- to three-week growth experiment under excess humidity and recovery conditions.Results and discussionG. biloba exhibited a smaller decrease in photosynthetic function in response to air pollution and soil salinity stress than R. pulchrum did, confirming its robustness to diverse environmental stresses. The low stomatal density, sunken stomata, and thick mesophyll of G. biloba contributed to its high tolerance of photosynthetic function to air pollution stress. The low stomatal density, and likely low proportion of xylem conduit, caused photosynthetic function of G. biloba to be less sensitive to soil salinity stress. Conversely, G. biloba plants grown under excess humidity exhibited reduced leaf mesophyll development, negatively impacting photosynthesis. This suggests that G. biloba does not possess high tolerance to excess humidity.